Association Between Vertebral Dimensions and Lumbar Modic Changes. Issue 7 (1st April 2021) - Julin, Modarress; Saukkonen, Jesperi; Oura, Petteri; Junno, Juho-Antti; Niemelä, Maisa; Määttä, Juhani; Niinimäki, Jaakko; Jämsä, Timo; Korpelainen, Raija; Karppinen, Jaro
Abstract : Study Design: Population-based birth cohort study. Objective: The aim of this study was to evaluate the relationship between vertebral dimensions and lumbar MC. Summary of Background Data: Low back pain (LBP) has become the leading cause of disability worldwide. Modic changes (MC) of the lumbar spine are one potential LBP-associated etiological factor. Mechanical stress is considered to play a key role in the development of MC through damage to endplates. There is speculation that vertebral dimensions play a role in some degenerative changes in the spine. Previous studies have also shown a positive association between moderate-to-vigorous physical activity (MVPA) and both vertebral dimensions and MC. In this study, we aimed to evaluate the relationship between vertebral dimensions and MC. Methods: The study population consisted of 1221 participants from the Northern Finland Birth Cohort 1966 who underwent lumbar magnetic resonance imaging (MRI) and physical activity measurements at the age of 46–48. The presence of Type 1 (MC1) and Type 2 (MC2) MC and the height, axial cross-sectional area (CSA), and volume of the L4 vertebra were determined from MRI scans. MVPA (≥3.5 metabolic equivalents) was measured by a wrist-worn accelerometer. We analyzed the association between lumbar MC and vertebral height, CSA, and volume using logistic regression models before and after adjustment for sex, height, weight, smoking, education level, and MVPA. Results: Vertebral height was positively associated with the presence of MC2 (odds ratio [OR] 3.51; 95% confidence interval [CI] 1.43–8.65), whereas vertebral CSA was not associated with the presence of lumbar MC. Vertebral volume was positively associated with the presence of any MC (OR 1.04; 95% CI 1.00–1.07), but the association did not persist when analyzing MC1 and MC2 separately. Conclusion: Vertebral height was associated with the presence of MC2. Further studies are needed to clarify the role of vertebral dimensions as independent risk factors for MC. Level of Evidence: 3 Abstract : In this study we evaluated the relationship between vertebral dimensions and lumbar Modic changes (MC). Vertebral height was associated with the presence of type 2 MC supporting earlier findings that larger vertebrae may be associated with degenerative changes of the lumbar spine.